2005
DOI: 10.1079/asc40450289
|View full text |Cite
|
Sign up to set email alerts
|

The development of harmful social behaviour in pigs with intact tails and different enrichment backgrounds in two housing systems

Abstract: The present study compared the performance and development of adverse behaviours of pigs with intact tails, when housed in a straw-bedded system or a part-slatted system enriched with a commercial device. The pigs had previously received different enrichment treatments (rooting box, liquid dispenser, straw bedding or none), either in the farrowing crate or with their lactating dam or post weaning. The pigs were mixed in groups at 10 weeks of age and from then on, every 2 weeks, behavioural observations were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
72
0
13

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(97 citation statements)
references
References 31 publications
8
72
0
13
Order By: Relevance
“…A decreased activity to age was in agreement with findings of Jensen et al (2010) (~40 and 90 LW) and van de Weerd et al (2005). In the current study, percentage of active time spent on straw-directed behaviour decreased from 33.8% to 26.2% from 40 to 80 kg LW.…”
supporting
confidence: 92%
“…A decreased activity to age was in agreement with findings of Jensen et al (2010) (~40 and 90 LW) and van de Weerd et al (2005). In the current study, percentage of active time spent on straw-directed behaviour decreased from 33.8% to 26.2% from 40 to 80 kg LW.…”
supporting
confidence: 92%
“…Tail-biting can be considered as a redirected behaviour, following the theory that in the absence of rooting material manipulative behaviours are redirected to pen-mates and may develop into harmful social behaviours. This has been supported by a number of studies which have shown that providing straw can reduce the levels of tail-biting (Beattie et al, 1995;Day et al, 2002a;Zonderland et al, 2004;Van de Weerd et al, 2005;Van De Weerd et al, 2006;Scott et al, 2007a) and other harmful social behaviour such as aggression (Ruiterkamp, 1985;Beattie et al, 1996;O'Connell and Beattie, 1999;Beattie et al, 2000b), bellynosing (Petersen et al, 1995) and nosing, chewing or biting pen-mates (Fraser et al, 1991b;Beattie et al, 1995;Simonsen, 1995;Beattie et al, 2000b). Straw also provides a pig with roughage and thermoregulatory control at cold temperatures.…”
Section: Introductionmentioning
confidence: 84%
“…Low frequencies of fighting following weaning in this study may have a number of reasons. First, the piglets that formed the new groups were acquainted during lactation, which is known to reduce fighting after mixing (Pitts et al, 2000;Weary et al, 2002;D'Eath, 2005); second, at weaning, these piglets were housed in a large enclosure with relatively low density, where they had the opportunity to root, which is known to reduce peer-directed behaviours (Van de Weerd et al, 2005). Additionally, because of the higher environmental stimulus, outdoor piglets play more during the lactation period (Johnson et al, 2001;Hö tzel et al, 2004), which is also thought to reduce fighting after weaning (O'Connell and Beattie, 1999).…”
Section: Discussionmentioning
confidence: 99%